The ancient novel and beyond - Panayotakis, Stelios, 1968-; Zimmerman, M. (Maaike); Keulen, Wytse Hette (Brill, 2003)
This work comprises the revised versions of selected papers read at the International Conference on the Ancient Novel (Groningen, July 2000). The essays combine judicious use of literary theory with traditional scholarship, and examines the ancient novels and related texts.
Keywords: Classical fiction -- History and criticism.; Literature, Medieval -- Classical influences.; Literature, Modern -- Classical influences.; Roman ancien -- Histoire et critique.; Littérature médiévale -- Influence ancienne.; Littérature -- Influence grecque.; TRAVEL -- Special Interest -- Literary.; LITERARY CRITICISM -- General.; Classical fiction; Literature, Medieval -- Classical influences; Literature, Modern -- Classical influences; Rezeption; Literatur; Roman; Romans.; Klassieke talen.; Klassieke oudheid.; Literatura clássica (história e crítica); Groningen <2000>; Latein.; Griechisch.; Criticism, interpretation, etc.